2014
DOI: 10.4103/0300-1652.132049
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of Citrus sinensis and carbimazole on serum T 4 , T 3 and TSH levels

Abstract: Background:There are previous independent reports on the anti-thyroid property of Citrus sinensis. This isoflavones and phenolic acid-rich natural agent is widely consumed as dietary supplement, thus the need to investigate its comparative effect with a standard anti-thyroid drug on T4, T3 and thyroid stimulating hormone (TSH) levels.Objective:To compare the effect of Citrus sinensis and carbimazole (CARB) on blood levels of thyroid hormones (T4 and T3) and TSH.Materials and Methods:Male wistar albino rats wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…Result in this study regarded the levothyroxine was in accordance with study by (Uduak et al, 2014) who found that LVT significantly reduced TSH while increasing T3and T 4 level. LVT is identical to that produced naturally in the thyroid gland.…”
Section: Fig 3 : Thyroid Stimulating Hormone Levelssupporting
confidence: 89%
“…Result in this study regarded the levothyroxine was in accordance with study by (Uduak et al, 2014) who found that LVT significantly reduced TSH while increasing T3and T 4 level. LVT is identical to that produced naturally in the thyroid gland.…”
Section: Fig 3 : Thyroid Stimulating Hormone Levelssupporting
confidence: 89%
“…In forth group decrease concentration of T4 and T3 hormones compared with the first group, that maybe due to known mechanism of carbimazole to inhibit peroxidase enzyme TPO action which it an important enzyme in the synthesis of thyroid hormones (8). Third group in which grape seed extract(GSE) interferes with drug, so that maybe explain the reason that T4 hormone level in this group closer to normal rang than its level in the first group maybe due to GSE flavonoids, Flavonoids have the ability to inhibit the action of and D1 deiodinase enzyme that converts T4 to T3 in liver this arise the level of T4 (7,16).What mention above may explain that there is an decrease in the level of the TSH hormone reached to the significant degree(P<0.05) in the first group compared with the control, while it did not in the third group, Because it is known that there is an inverse relationship between the level of hormone TSH and the level of thyroid hormones according to the negative feedback mechanism (7).…”
Section: Effect Of L-thyroxine and Gse In (Tsh T4 T3)mentioning
confidence: 99%
“…Another in vivo study investigated the antithyroid effects of Citrus sinensis (fresh orange juice) in male Wistar albino rats. C. sinensis (1500 mg/kg, once daily, for 28 days) reduced T4 levels and increased TSH levels, suggesting that fresh orange juice may be an adjuvant for the treatment of hyperthyroidism …”
Section: Phytochemicals Modulating Thyroid Signaling and Their Role Imentioning
confidence: 99%
“…While the mechanisms underlying the modulatory effects of soy or soy isoflavones on thyroid signaling have been described in several in vivo and in vitro studies, the reported effects are somewhat inconsistent with observations in human studies. In particular, in vivo studies in rodents have reported a decrease in thyroid signaling (and TH levels in particular) upon exposure to certain phytochemicals or plant extracts (e.g., Annona squamosa seed extract or quercetin, coumarin, E. officinalis Gaertn., piperine, rutin, naringin and hesperidin, fresh orange juice, genistein and daidzein, BH, PSCs, and stigmasterol), while others have shown an increase in TH levels occurring upon exposure to other phytocompounds (e.g., guggulu, several phytosterols, fermented and nonfermented isoflavones, and peel extracts of the fruits of M. indica , C. melo , and C. vulgaris ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%